Pelatihan Pengelasan Bagi Pemuda Karang Taruna Sengkol Kelurahan Muncul – Setu Tangerang Selatan - Wawan Budiarto; Ahsonul Anam; Gadang Priyotomo (CV. Multi Kreasi Media, 2022)
The implementation of this activity is related to the application of the benefits of science related to welding techniques. Through this community service activity, it is targeted to provide benefits for youth who are members of youth organizations by carrying out welding training. The training provided is welding technical guidance by providing material, discussion questions and answers and practicing welding examples.